Heart transplantation in patients undergoing extracorporeal cardiopulmonary resuscitation in in‑hospital cardiac arrest - V. N. Poptsov; E. A. Spirina; A. K. Solodovnikova; A. S. Epremyan; A. A. Kuznetsova; A. S. Ignatkina; G. B. Glinkin; S. A. Budagaev (Вестник трансплантологии и искусственных органов, 2025)
Objective: to analyze heart transplant (HT) outcomes in patients who suffered cardiac arrest requiring extracorporeal cardiopulmonary resuscitation (ECPR) by peripheral veno-arterial extracorporeal membrane oxygenation (VA-ECMO). Materials and methods. The study included 41 patients (14 (34.1%) women and 27 (65.9%) men, aged 42.6 ± 16.8 (40.0 [30.5; 54.0]) years with in-hospital cardiac arrest. The causes of cardiac arrest were acute decompensated heart failure (n = 19; 46.3%), irreversible graft dysfunction (n = 9; 22.0%), postcardiotomy acute heart failure (n = 5; 12.2%), acute myocardial infarction (n = 4; 9.8%), and acute graft rejection (n = 4; 9.8%).Results. Twenty-seven (65.9%) patients had cardiac arrest in the intensive care unit (ICU) and 14 (34.1%) outside ICU. The interval between femoral artery puncture and ECPR initiation was 4-17 (9 ± 5) minutes, while that between cardiopulmonary resuscitation (CPR) initiation and peripheral VA-ECMO was 26 ± 9 minutes. Atonic seizure developed in 11 (26.8%) of 41 patients while receiving VA-ECMO. Of the 41 patients, 30 (73.2%) had irreversible brain damage. Four (9.8%) patients were discharged from the hospital without neurological or multiple organ dysfunction. In 26 (63.4%) patients (10 (38.5%) women and 16 (61.5%) men) aged 14 to 63 (40.7 ± 15.8) years, ECPR and subsequent treatment resulted in survival to HT while receiving VA-ECMO (duration 1-11 (4.0 [1.5; 5.0]) days). The age of the heart donor (6 (23.1%) women and 20 (76.9%) men) was 44.0 ± 9.9 years, the cumulative Eurotransplant Heart Donor Score was 16.9 ± 2.7, the Donor Risk Index was 6.3 ± 1.5, and the estimated incidence of severe primary graft dysfunction (RADIAL scale) was 15.4 ± 3.7%. Graft ischemia lasted for 188 ± 72 (170.0 [141.25; 185.0]) minutes. Five (19.2%) recipients developed severe dysfunction, which required continuation of peripheral VA-ECMO in the postperfusion period. The cause of death (n = 4; 15.3%) in the early post-HT period was irreversible multiple organ dysfunction.Conclusion. In-hospital survival after emergency HT in recipients who underwent ECPR before transplantation is 84.7%.